Disordered eating behaviors in rhythmic gymnasts: a survey to investigate the coaches` point of view on the management. - Di Cagno, A.; Fiorilli, G.; Iuliano, E.; Tsopani, D.; Buonsenso, A.; Piazza, M.; Calcagno, G. (Journal of Physical Education and Sport, 2018)
Purpose: The aim of the present study was to investigate the coaches` point of view on the rhythmic gymnasts` disordered eating behaviors, by focusing the attention on their knowledge of this problem, in relation to training and competition participation. The second aim is to assess if there is theoretical and/or practical collaboration between coaches and medical staff. Methods: One hundred and Sixty-nine rhythmic gymnastics coaches completed a 23 items questionnaire, based on the NCAA survey (National Collegiate Athletic Association). All the coaches had 15.2 ± 9.6 years of experience in coaching. Paired T-Test was used to compare the impact of disordered eating behaviors on health and performance and Chi-Squared analysis was used to compare different outputs obtained in the answers. Results: Coaches declared to have identified an average of 1.3 ± 1.7 symptomatic gymnasts during their careers, and 25% of them affirmed to have no good knowledge of the problem. Participants were informed that disordered eating behaviors may negatively influence both health and sport performance. About 88% of the coaches were aware that current eating disorders influence the decision to recruit an athlete. Ninety-one percent of the coaches never referred to a professional mental health. Conclusion: Coaches understood seriousness of the problem, even though the majority of the coaches did not refer to a therapist. It was recommended, instead, a multidisciplinary approach for a correct management, including coaches, psychologists and nutritionists.